Scientific Rationale for Waiving Clinical Efficacy Testing of Biosimilars - Niazi S (Dove Medical Press, 2022)
Sarfaraz Niazi Department of Pharmaceutical Sciences, College of Pharmacy, University of Illinois, Chicago, IL, USACorrespondence: Sarfaraz Niazi, Email niazi@niazi.comAbstract: After 18 years and the administration of billions of doses, there is little doubt about biosimilars' safety and efficacy. Yet, only 14 molecules in the EU and 9 in the US are available as biosimilars, among the 200+ targets, due mainly to the high development cost attributed to clinical efficacy testing after extensive analytical assessment, nonclinical testing, and clinical pharmacology comparisons. So far, none of the hundreds of clinical efficacy testing has failed because it cannot fail due to its lack of sensitivity for multiple reasons, as argued in this paper. This analysis is unique since biosimilars are the first category of products that are put to comparative testing as if these were new biological drugs. Clinical efficacy testing used to overcome differences in the analytical, nonclinical, and clinical pharmacology comparisons can lead to the approval of unsafe products. Only recently the regulatory agencies have begun to talk about this risk and shown their willingness to waive these studies. However, a clear change in the regulatory guidelines is required to change the mindset of all biosimilar stakeholders to bring a pivotal change in the availability of affordable biosimilars.Keywords: biosimilars, clinical efficacy testing, BPCIA, biosimilarity, FDA, EMA, clinical equivalence